2021
DOI: 10.2147/dddt.s310760
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticle-Coated Ethyl Cellulose Inhibits Tumor Necrosis Factor-α of Breast Cancer Cells

Abstract: Introduction: Cancer is one of the leading causes of death worldwide. In many cases, cancer is related to the elevated expression of a significant cytokine known as tumor necrosis factor-α (TNF-α). Breast cancer in particular is linked to increased proliferation of tumor cells, high incidence of malignancies, more metastases, and generally poor prognosis for the patient. The research sought to assess the effect of silver nanoparticles reduced with ethyl cellulose polymer (AgNPs-EC) on TNF-α expression in MCF-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…The anticancer action of the nanocomposite can be connected to the induction of apoptosis in MCF-7 cells via blocking the activation and nuclear translocation of TNF-mRNA and protein expression. TNF-induced inflammation and toxicity are both exacerbated by AgNPs-EC [80,81].…”
Section: Effect Of Nanocellulose and Au/cellulose Nanocomposite On Raf-1 Gene And P53 Gene Expressionmentioning
confidence: 99%
“…The anticancer action of the nanocomposite can be connected to the induction of apoptosis in MCF-7 cells via blocking the activation and nuclear translocation of TNF-mRNA and protein expression. TNF-induced inflammation and toxicity are both exacerbated by AgNPs-EC [80,81].…”
Section: Effect Of Nanocellulose and Au/cellulose Nanocomposite On Raf-1 Gene And P53 Gene Expressionmentioning
confidence: 99%
“…e era of nanomedicine and nanoparticulate drug delivery systems has begun long ago and shown significant success in different fields, especially tumor diagnosis and treatment [4][5][6][7][8][9]. Nanoparticles directed at cancer have been shown to be promising materials in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Garcia et al [ 59 ] also reported a similar result. Regarding AgNPs-EC, it was reported in our research group that the negatively charged EC facilitates the attraction of Ag+ to the EC chains, followed by reduction with the present, reducing groups in the polymer chain [ 49 ]. In addition, the observed surface plasmon resonance of the produced NPs shifted to a higher wavelength than the AgNO 3 value (the reported λ max , 390 nm), following other researchers [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the use of surface stabilizing agents for AgNPs dispersions is mandatory. Polyvinyl pyrrolidone (PVP), polyethylene glycol (PEG), and ethyl cellulose (EC) are amongst the most popular stabilizing agents for AgNPs dispersion due to their good biocompatibility and low cytotoxicity [ 47 , 48 , 49 , 50 ]. In addition, as previously mentioned, AgNPs stabilized with PVP and EC showed proven antibacterial properties, especially with highly resistant strains of E. coli .…”
Section: Introductionmentioning
confidence: 99%